Ethical Ideologies and Older Consumer Perceptions of Unethical Sales Tactics - Ramsey, Rosemary P. (Journal of business ethics, 2007)
Demographic differences among consumer groups have become increasingly important to the development of marketing strategies. Marketers depend heavily on the sales force to implement strategies at the consumer level and, not surprisingly, different groups may view the salesperson’s role differently. Unfortunately, unethical sales practices targeted at various consumer groups, and especially at seniors, have been utilized as well. The purpose of this study is to provide initial empirical evidence of the ethical ideological make-up of four age segments outlined by Strauss and Howe (1991, Generations: The History of America’s Future 1584–2069, Morrow, New York) and to examine the propensity for these groups (seniors, in particular) to respond differentially to potentially unethical sales tactics. Data were collected from 179 respondents representing the four generational age groups. MANOVA revealed that the seniors in this study were distinct with respect to ethical ideology and less accepting of unethical sales tactics. Managerial implications are discussed for sales organizations to maximize their effectiveness across consumer groups.